Determination of Clastogenic and Anticlastogenic Potential of Cuminum Cyminum Seed Oil Using in Vitro Micronucleus Assay in CHO-K1 Cells. Issue 3 (3rd July 2019) - Goyal, Vinod Kumar; Vincent, Sthevaan; Pandey, Santosh Kumar; Nirogi, Ramakrishna
ABSTRACT: Cumin ( Cuminum cyminum ) was evaluated for its clastogenic and anticlastogenic potentials using a micronucleus assay in CHO-K1 cells. No increase in micronuclei was observed at any tested concentrations compared to concurrent vehicle control, indicating that cumin seed oil did not have clastogenic potentials under test condition. To determine the anticlastogenic potential of cumin, another trial was conducted against the potential clastogenic agents; cumin did not show any anticlastogenic activity against the used clastogens.